ANALISIS KINERJA EKSPOR TEMBAKAU DI INDONESIA: PENDEKATAN VECTOR AUTOREGRESSION - Badara Shofi Dana; Achmad Fawaid Hasan (UPT Penerbitan Universitas Jember)
This study aimed to analyze the value of the rupiah against the US dollar, the world tobacco price and production quantities of tobacco on tobacco in Indonesia's export performance in the long term and short term. Research approach uses vector autoregression (VAR). The sample used in this research that the Indonesian nation as a whole. The empirical results of this study indicate that the value of the rupiah against the US dollar, the price of the world's tobacco and production quantities of tobacco influence significant to exports of tobacco in Indonesia in the long term and short term.